Coastal Dunes Formation Due to Fluvial and Wind Reaction, Special Reference to East Coast in India - Arun Santra (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
A dune is a shape of land formed of an immense volume of windy sand. In deserted ecosystems like the Sahara and close to the beaches, dunes are most natural. A dune system is considered a region of dunes. Wind and water will dynamically drift the dunes, which can have extreme implications. The dune is a hill of free sand constructed by aeolian processes (wind) or water movement in physical geography. The dunes are created by contact with the movement of air or water of various ways and sizes. However, human-made dunes may be artificial. In a stem (up-flow) line, where sand drives the dune has a shorter "slip face" and most forms of dunes are longer in the lee side. The dunes are called a valley or trough. A wide, flat region of shallow sand and/or dunes with little or no vegetation has an erg or sandy shore. Dune fields are considered narrower zones. In certain mountains, inland and around the beaches, dunes take shape. Any marine regions have one or two dunes flowing immediately inland from the ocean parallel to the coastline. The dunes are also necessary to shield the soil from possible ravages from sea storm waves. Though coastal areas are the most commonly spread dunes, inland in dry areas are the greater dune complexes synonymous with old lake or sea beds. Dunes can form on sand or gravel beds of river, estuaries and the sea bed under the action of water flow (in fluvial processes). The coastal sands of dolls are hips and strips created by degraded, terrestrial; oceanic sections of sand and ground rock. This is known as a specialised environment that is marked by living conditions such as high salt, low humidity and low organic matter. However, different species of flora, fauna and microorganisms adapted uniquely to certain conditions still exist in dunes. In the rhizosphere, phyllosphere, and indoor plants that are extremely important for incorporating dunes, microbial classes including fungi, bacteria, and actinobacteria are very abundant. A number of bioactive metabolites, which are essential for agriculture and industry, were found to be generated by microorganisms in this environment. Many species of shrubs and rhizobic fungi associated with dune plants are prolific plant growth producers that encourage biochemical sources such as indole acetic acid. This study analyses coastal dunes formation due to fluvial and wind reaction with particular reference to East Coast in India.